Feature cytokine metabolism in patients with acute viral meningitis - Nartov, P (Annals of Mechnikov's Institute, 2020)
Introduction. The urgency of the problem of viral meningitis etiology is due to the high frequency of severe forms of the disease, significant levels of mortality, spread spectrum etiopatogenia, the difficulty of differential diagnosis. The leading role in the pathogenesis of CNS is given to pathological processes that occur in Sabar mi area, i.e. the blood-brain barrier and causes changes intrathecal homeostasis. The height of the inflammatory syndrome and release of anti-inflammatory cytokines (CK), as well as alternative Pro-inflammatory patients of acute viral meningitis (AVM) associated with the penetration into CSF infectious pathogen or molecular patterns, which act as trigger cells of the immune response. Materialandmethods. 26 patients were examined with a diagnosis of GUM who was admitted on an emergency basis in regional clinical infectious diseases hospital, Kharkov. The age of patients ranged from 17 to 65 years, and was dominated by persons younger than 40 years (the average age of women was 37 years, and 25 for men). The majority of patients with GUM was identified enterovirus and herpesvirus etiology of the disease: in 9 patients were diagnosed with enteroviral meningitis, and 12 patients herpesviruses meningitis (HSV-1/2–7, VZV–1, EBV–1, CMV–2, HHV-6–1). The diagnosis was verified on the basis of clinical and lquiroga, serological and molecular genetic studies. The research material was cerebrospinal fluid (CSF) of patients GUM which was received in early disease and in the recovery period. The concentration of GC (IL– 1, 2, 4, 6, 10 and TNF-α) in CSF were determined by ELISA method. The control group consisted of 11 individuals with intact CSF. The results are statistically processed on a computer using standard computer programs (Excel and Statistica 6. Resultsanddiscussion. In the acute period of the disease, patients AVM GC content that were studied, were significantly higher compared with the control group: TNF-α – 8.7-fold (p <0.05), IL-1 – 6.7-fold (p <0.05), IL-2 – 10.4 times (p <0.05), IL-4 – 3.5 times (p <0.05), IL-6 – 2.3 times (p <0.05) and IL-10 – 4.4-fold (p <0.05). Regarding the concentration of GC in the period of convalescence: NEF-α was higher than the control value 5.8-fold (p <0.05), IL-1 – 3.7 times (p <0.05), IL-2 – 6.2 times (p<0.05), IL-4 2.7 times (p <0.05), IL-6 2.2 – fold (p <0.05), IL-10 – 2.7 times (p <0.05). In connection with monodirectional changes in cytokines exchange in the form of increased levels of both inflammatory and anti-inflammatory cytokines, to assess the nature of compensatory mechanisms between inflammatory and anti-inflammatory was used normalized indicator – t-test. The degree of activity of inflammatory CK in the acute period of the disease was only 15% higher in comparison with indicators of the Central Committee of anti-inflammatory. This indicates a balance of both classes of the Central Committee and on the functioning of cytokine exchange in the direction normocapnic. To understand the compensatory capacity of cytokine exchange in the period of convalescence was also assessed the balance between inflammatory and anti-inflammatory activity of the Central Committee of the inflammatory activity of the Central Committee slightly (15.9%) was higher than the rates of inflammatory CK. So, inflammatory and anti-inflammatory CK in CSF of patients GUM in the period of convalescence also balanced, and their functions are normocapnic. Conclusion. Patients with AVM in the dynamics of the disease, the increase in the levels of proinflammatory (IL-1, IL-2, IL-6, TNF-α) and antiinflammatory (IL-4, IL-10) cytokines compared with control, and also pathogenetic balance (normocapnia) cytokines. The increase in the GA concentration in the acute phase GUM evidence of both the existence of laws neurontina processes and peculiarities, caused by the pathogen, and an increase in the stage of convalescence – preservation of intrathecal inflammation. Research in CSF in the CNS allows not only to clarify the pathogenesis of the disease, but in the long term to make a differential diagnosis between serous and purulent nature of inflammation of the meninges, to predict the severity of disease.